2009
DOI: 10.1093/abbs/gmp007
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and functional analysis of the human glioblastoma-specific promoter region of the human GD3 synthase (<italic>hST8Sia I</italic>) gene

Abstract: We identified the promoter region of the human GD3 synthase (hST8Sia I) gene to elucidate the mechanism underlying the regulation of hST8Sia I expression in human glioblastoma cells. The 5 0 -rapid amplification of cDNA end using mRNA prepared from U-87MG cells revealed the presence of transcription start site of hST8Sia I gene, and the 5 0 -terminal analysis of its product showed that transcription started from 648 nucleotides upstream of the translational initiation site. Functional analysis of the 5 0 -flan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 22 publications
0
25
0
1
Order By: Relevance
“…Similar aberrant non-coding transcripts have recently been described in tumors and have been suggested to play functional roles in cancer progression and metastasis [34]. Interestingly, the core promoter we identified in breast cancer cells, between −923 and −565 upstream the initiation codon, overlaps with the core promoter found in melanoma (−833/−519) [24] and neuroblastoma (−1190/−690) [27] but not with the one found in glioblastoma (−1330/−1190) [26], suggesting a tissue-specific regulation of ST8SIA1. …”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Similar aberrant non-coding transcripts have recently been described in tumors and have been suggested to play functional roles in cancer progression and metastasis [34]. Interestingly, the core promoter we identified in breast cancer cells, between −923 and −565 upstream the initiation codon, overlaps with the core promoter found in melanoma (−833/−519) [24] and neuroblastoma (−1190/−690) [27] but not with the one found in glioblastoma (−1330/−1190) [26], suggesting a tissue-specific regulation of ST8SIA1. …”
Section: Discussionmentioning
confidence: 67%
“…ST8SIA1 is located on chromosome 12, in p12.1-p11.2 locus and consists in five coding exons spanning over 135 kbp [24]. Several reports have described the 5′-untranslated region (5′-UTR) of ST8SIA1 in melanoma [24], [25], glioblastoma [26] and neuroblastoma [27] cell lines, showing a unique transcript with transcription start sites (TSS) located 400 to 650 bp upstream the initiation codon on the first exon. In this study, we described the main ST8SIA1 transcript expressed in breast cancer tumors and cell lines and we characterized the core promoter of this gene.…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis indicates that only GD3S and not GD2S mRNA expression was regulated during EMT. Moreover, Dae et al found that ZEB1, a known EMT-inducing transcription factor, directly binds to the GD3S promoter and induces transcription of GD3S in glioblastoma cells (32). These findings suggest that the EMT-inducing factors such as ZEB1 might bind to the GD3S promoter and upregulate its expression in CSCs as well as in EMT-derived cancer cells, which then generate GD3, due to the high basal expression of GD2S in these cells, which probably immediately converts to GD2 by ubiquitously expressed GD2S.…”
Section: Discussionmentioning
confidence: 99%
“…During TGFβ-induced EMT, the mothers against decapentaplegic homolog 3 and 4 (Smad3-Smad4) complex represses B3GALT4 by binding to its promoter (Guo et al, 2015), whereas zinc finger E-box-binding homeobox 1 (Zeb1) (a transcriptional target of Smad3-Smad4) binds to and activates the promoters of both ST3GAL5 (Mathow et al, 2015) and ST8SIA1 (Dae et al, 2009). Importantly, exogenous provision of GA1 (one of the products of B3GALT4/GA1 synthase) inhibits TGFβ-induced EMT, which suggests that GSLs are both targets and regulators of the same signaling pathway (Guan et al, 2009;Guo et al, 2015) ( Fig.…”
Section: The Regulatory Circuits Of Gsl Expressionmentioning
confidence: 99%